(untitled) (LACCEI, 2024)
We have designed and docked derivatives of a new anti-inflammatory compound into the crystal structure of the Lipoxygenase-5 (LOX-5) enzyme. We found that four derivatives have the same ability to inhibit the activity of the enzyme as the anti-inflammatory drug Zileuton. This information may help us develop new compounds to treat inflammation.